Gender equality and health equity: strategic lessons from country experiences of gender mainstreaming in health - Ana Cristina González Vélez; Anna Coates; Victoria Diaz Garcia; Denisse Wolfenzon (Pan American Health Organization, 2020)
Objectives. To analyze progress in organizational structures, mechanisms, strategies, and enabling factors and barriers towards gender mainstreaming (GM) in health in Guatemala, Guyana, and Peru, given GM's role in addressing gender inequalities in health as a key structural driver of health equity. Methods. Data was obtained through a grey literature review of laws, policies, and/or program documents and semi-structured qualitative interviews with 37 informants. Analysis was based on a theoretical framework including 7 categories considered essential to advance GM in the health sector. Results. Despite significant efforts and accumulated experiences of GM in health, structural barriers include: wider societal challenges of transforming gender unequal power relations; health system complexity combined with the low technical, political, and financial capacity of institutional structures tasked with GM; and limited coordination with (often weak) National Women's Machineries (NWMs). In some contexts, barriers are compounded by limited understanding of basic concepts underlying GM (at times exacerbated by misunderstandings related to intersectionality and/or engagement with men) and the absence of indicators to measure GM's concrete results and impact. Conclusions. Successful GM requires a more strategic and transformational agenda, developed and implemented in coordination with NWMs and civil society and with reference to external bodies (e.g. Committee on the Elimination of Discrimination against Women) to go beyond process, with clearer distinction between gender sensitivity and gender transformation, and definition of expected results and indicators to measure advances. These then could be better documented and systematized, enabling GM to be more broadly understood and operationalized as a concrete instrument towards health equity.